2016
DOI: 10.1021/acs.joc.6b01616
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Mediated Formation of Chiral Carbamates from meso-Epoxides via Polycarbonate Intermediates

Abstract: Carbon dioxide has attracted broad interest as a renewable C1 feedstock for efficient transformation into value-added organic chemicals; nevertheless, far less attention was paid to its stereochemically controlled catalytic fixation/conversion processes. Here, we report a new strategy for the selective synthesis of chiral carbamates from carbon dioxide via polycarbonate intermediates, which are formed by the desymmetric copolymerization of meso-epoxides using enantiopure dinuclear Co(III) catalyst systems with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…[20b] TheL ul aboratory reported as imilar concept for chiral carbamate synthesis from meso-epoxides using an enantiopure dinuclear Co III catalyst. [21] Cyclic carbonates also can be used as effective acylation reagents for amines toward the preparation of five-membered cyclic carbamates,a lso known as oxazolidinones. [22] Ionic liquids (ILs) are the most frequently used catalysts for these transformations.For example,the Gao group reported that 1butyl-3-methyl-imidazolium acetate (BmimOAc) acts as an efficient catalyst for the acylation of anilines using ethylene carbonate.…”
Section: Carbamates Via Ring-opening Chemistrymentioning
confidence: 99%
“…[20b] TheL ul aboratory reported as imilar concept for chiral carbamate synthesis from meso-epoxides using an enantiopure dinuclear Co III catalyst. [21] Cyclic carbonates also can be used as effective acylation reagents for amines toward the preparation of five-membered cyclic carbamates,a lso known as oxazolidinones. [22] Ionic liquids (ILs) are the most frequently used catalysts for these transformations.For example,the Gao group reported that 1butyl-3-methyl-imidazolium acetate (BmimOAc) acts as an efficient catalyst for the acylation of anilines using ethylene carbonate.…”
Section: Carbamates Via Ring-opening Chemistrymentioning
confidence: 99%
“…[ [21] Cyclische Carbonate kçnnen als wirksame Acylierungsreagenzien fürA mine zur Herstellung von fünfgliedrigen cyclischen Carbamaten (Oxazolidinonen) verwendet werden. Einfache Va riationen der fürdie Epoxid/CO 2 -Kupplung vorteilhaften Reaktionsbedingungen führten entweder zu oligomeren oder cyclischen Carbonat-Zwischenstufen.…”
Section: Carbamate Via Ringçffnungschemieunclassified
“…[18] Interessanterweise erwies sich ein solches Protonen-Relais-System fürd ie regioselektive Aminolyse von zwei-oder dreifach substituierten cyclischen Carbonaten mit Alkylaminen als geeignet (Schema 2, Wegb). [ [21] Cyclische Carbonate kçnnen als wirksame Acylierungsreagenzien fürA mine zur Herstellung von fünfgliedrigen cyclischen Carbamaten (Oxazolidinonen) verwendet werden. [22] Die am häufigsten eingesetzten Katalysatoren für diese Art von Umwandlungen sind ILs.B eispielsweise berichteten Gao und Mitarbeiter, dass 1-Butyl-3-methylimidazoliumacetat (BmimOAc) ein wirksamer Katalysator fürdie Acylierung von Anilinen unter der Verwendung von Ethylencarbonat ist.…”
Section: Carbamate Via Ringçffnungschemieunclassified
“…[37][38][39] The area of cyclic carbonate synthesis has witnessed a spectacular growth over the last decade 2,3,30-32 with a primary focus on the development of improved and more sustainable catalysts for the [3+2] cycloaddition of epoxides and CO2. [40][41][42][43] The (dia)stereoselective formation of more complex cyclic organic carbonates, 25,44,45 however, remains underdeveloped. It is generally assumed that the formation of a cyclic carbonate from epoxides and CO2 follows a typical threestep sequence involving epoxide ring opening induced by the (binary) catalyst, subsequent activation of the CO2 molecule by the intermediate alkoxide and termination through cyclization releasing the desired product.…”
Section: Introductionmentioning
confidence: 99%